Over a million students use our free study notes to help them with their homework
x+10=0x= -10x-16=0x= 16
Multiplying out the first two brackets gives (x^2-x-12)(x+5). Multiplying the remaining brackets gives x^3 + 4x^2 -17x - 60.a = 4b = 60
We must use the substitution method for this question because the first equation is a quadratic. Take the more simple equation (the second one), and use that to substitute the value for y in to the first ...
Using the product rule (u'v+v'u, where u and v are the chosen substitutes) to find the first derivative will be dy/dx=x'=2xe^(-2x)+x^(2)e^(-2x)(-2)=2xe^(-2x)(x-x^2). This will give the d...
To solve these simultaneous equations there are two different methods that could be used. The first one to try in this case is to start with rearranging one of the equations to get a value of y by itself....
←
569
570
571
572
573
→
Internet Safety
Payment Security
Cyber
Essentials